2021
DOI: 10.1186/s43141-021-00164-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunocontraceptive potential of a GnRH receptor-based fusion recombinant protein

Abstract: Background The management of stray dog population has been of utmost importance due to their overpopulation, increase in dog bites incidence, and rabies. Contraceptive vaccines, a non-surgical alternative to spaying and neutering are viewed as a valuable option for the management of dog population. In this study, the contraceptive potential of a recombinant fusion protein containing the three genes GnRH, GnRH receptor, and ZP3 was explored. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In line with this, previous studies have shown that antigens containing multiple repeats of ZP3 epitopes stimulate higher antibodies in BALB/c mice compared with those containing single mZP3 epitopes [ 32 , 77 ]. Incorporation of multiple copies of epitopes into antigens has been investigated previously for various weak immunogens to enhance their immunogenicity [ 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, previous studies have shown that antigens containing multiple repeats of ZP3 epitopes stimulate higher antibodies in BALB/c mice compared with those containing single mZP3 epitopes [ 32 , 77 ]. Incorporation of multiple copies of epitopes into antigens has been investigated previously for various weak immunogens to enhance their immunogenicity [ 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, previous studies have shown that antigens containing multiple repeats of ZP3 epitopes stimulate higher antibodies in BALB/c mice compared with those containing single mZP3 epitopes (Sadler et al 2000;Hardy et al 2004). Incorporation of multiple copies of epitopes into antigens has been investigated previously for various weak immunogens to enhance their immunogenicity (Jinshu et al 2004;Haigh et al 2007;Sandam et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…containing single mZP3 epitopes(Sadler et al 2000;Hardy et al 2004). Incorporation of multiple copies of epitopes into antigens has been investigated previously for various weak immunogens to enhance their immunogenicity(Jinshu et al 2004;Haigh et al 2007;Sandam et al 2021).Notably, the production of mZP3 antigens in plants seems to increase immunogenicity compared to other production systems. E. coli-produced single mZP3-peptide antigens elicited no signi cant antibody responses to ZP3 in BALB/c immunized mice(Hardy et al 2004), and ZP3 protein expressed in the insect cell-expression system(Hardy 2003) seems to induce lower levels of antibodies against mZP3 peptide compared to our study.…”
mentioning
confidence: 99%